Training and calibration of interviewers for oral health literacy using the BREALD-30 in epidemiological studies - Karina Duarte VILELLA; Luciana Reichert da Silva ASSUNÇÃO; Mônica Carmem JUNKES; José Vitor Nogara Borges de MENEZES; Fabian Calixto FRAIZ; Fernanda de Morais FERREIRA
Abstract The objective of this study was to describe an interviewer training and calibration method to evaluate oral health literacy using the Brazilian Rapid Estimate of Adult Literacy in Dentistry (BREALD-30) in epidemiological studies. An experienced researcher (gold standard) conducted all training sessions. The interviewer training and calibration sessions included three different phases: theoretical training, practical training, and calibration. In the calibration phase, six interviewers (dentists) independently assessed 15 videos of individuals who had different levels of oral health literacy. Accuracy and reproducibility were evaluated using the kappa coefficient and the intraclass correlation coefficient (ICC). The percentage of agreement for each word in the instrument was also calculated. After training, the kappa values were higher than 0.911 and 0.893 for intra- and inter-rater agreement, respectively. When the results were analyzed separately for the different levels of literacy, the lowest agreement rate was found when evaluating the videos of individuals with low literacy (K = 0.871), but still within the range considered to be near-perfect agreement. The ICC values were higher than 0.990 and 0.975 for intra- and inter-rater agreement, respectively. The lowest percentage of agreement was 86.6% for the word "hipoplasia" (hypoplasia). This interviewer training and calibration method proved to be feasible and effective. Therefore, it can be used as a methodological tool in studies assessing oral health literacy using the BREALD-30.